KLRG1 and CD103 Expressions Define Distinct Intestinal Tissue-Resident Memory CD8 T Cell Subsets Modulated in Crohn's Disease - Bottois, Hugo; Ngollo, Marjolaine; Hammoudi, Nassim; Courau, Tristan; Bonnereau, Julie; Chardiny, Victor; Grand, Céline; Gergaud, Brice; Allez, Matthieu; Le Bourhis, Lionel (Frontiers in Immunology, 2020)
Intestinal tissue-resident memory CD8 T cells (Trm) are non-recirculating effector cells ideally positioned to detect and react to microbial infections in the gut mucosa. There is an emerging understanding of Trm cell differentiation and functions, but their implication in inflammatory bowel diseases, such as Crohn’s disease (CD), is still unknown. Here, we describe CD8 cells in the human intestine expressing KLRG1 or CD103, two receptors of E-cadherin. While CD103 CD8 T cells are present in high numbers in the mucosa of CD patients and controls, KLRG1 CD8 T cells are increased in inflammatory conditions. Mucosal CD103 CD8 T cells are more responsive to TCR restimulation, but KLRG1 CD8 T cells show increased cytotoxic and proliferative potential. CD103 CD8 T cells originate mostly from KLRG1 negative cells after TCR triggering and TGF stimulation. Interestingly, mucosal CD103 CD8 T cells from CD patients display major changes in their transcriptomic landscape compared to controls. They express Th17 related genes including CCL20, IL22 and IL26, which could contribute to the pathogenesis of CD. Overall, these findings suggest that CD103 CD8 T cells in CD induce a tissue-wide alert increasing innate immune responses and recruitment of effector cells such as KLRG1 CD8 T cells.